2016
DOI: 10.1039/c6ra19324b
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free synthesis of oxazoles: valuable structural fragments in drug discovery

Abstract: This review article encapsulates the recent developments in the metal-free approaches used to construct oxazole moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 161 publications
0
47
0
Order By: Relevance
“…A five‐membered heterocyclic aromatic ring compound, oxazole is one of the important platform having in a wide variation of biologically active compounds and natural products . In current years, its research has increase considerable attention from both industry and academia in view of its assorted pharmacological properties . Some oxazoles showed inhibitory activity of enzyme as well as against nitric oxide (NO) production in lipopolysaccharide (LPS)‐induced RAW 264.7 cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A five‐membered heterocyclic aromatic ring compound, oxazole is one of the important platform having in a wide variation of biologically active compounds and natural products . In current years, its research has increase considerable attention from both industry and academia in view of its assorted pharmacological properties . Some oxazoles showed inhibitory activity of enzyme as well as against nitric oxide (NO) production in lipopolysaccharide (LPS)‐induced RAW 264.7 cells .…”
Section: Introductionmentioning
confidence: 99%
“…Some oxazoles showed inhibitory activity of enzyme as well as against nitric oxide (NO) production in lipopolysaccharide (LPS)‐induced RAW 264.7 cells . The reports available on substituted oxazoles can be used as agrochemicals, fluorescent dyes, corrosion inhibitors and find applications in photography and polymer industries . In addition, they can assist as significant rout in organic synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Some oxazoles also exhibited enzyme inhibitory activity. It is reported that substituted oxazoles can be used as agrochemicals, fluorescent dyes, corrosion inhibitors and find applications in photography and polymer industries . In addition, they can serve as important synthons in organic synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, 2,5‐substituted aryl or alkyl oxazoles are privileged scaffolds found in numerous natural products and pharmaceutical agents . They have been investigated as antidiabetic, anticancer, and antibacterial agents …”
Section: Introductionmentioning
confidence: 99%
“…13,14 Among them, the cycloisomerization of N-propargyl amides has been widely employed as the effective and versatile synthesis of oxazoles (Scheme 3).…”
Section: -Iodane-mediated Cycloisomerization/functionalization Reactionsmentioning
confidence: 99%